Parenting - Merino, Noel. (Farmington Hills, MI : Greenhaven Press, 2010)
Presents extracts and analysis of four court decisions dealing with parenting, covering such issues as religious freedom, child abuse, the right of states to interfere with parental decisions, and who is legally a parent.
3. Troxel created the need for states to define parental unfitness / Daniel R. Victor and Keri L. Middleditch -- 4. Parental rights since troxel are in jeopardy / ParentalRights.org -- Troxel and other court rulings lack sufficient consideration of children's interests / Tracy Leigh Dodds -- Validating parental rights and obligations for biological, acting parents -- 1. The court's opinion : lesbians who donate eggs to their partners have parental rights and responsibilities / Carlos R. Moreno -- 2. Dissenting opinion : egg donors do not have parental rights and responsibilities / Joyce L. Kennard -- 3. Children have a right to continue parental relationships / Debra Back Marley and Robert C. Fellmeth -- 4. The court's reasoning in K.M. and other cases dealing with same-sex partners is sensible / Joanna Grossman -- 5. New reproductive technologies raise questions about legal parenthood / Gail Javitt.
Includes bibliographical references (p. 194-198) and index.
Keywords: Parent and child (Law) -- United States